AB0942 Efficacy and safety of subcutaneous anti-TNF alpha, etanercept and adalimumab, in elderly patients affected by psoriasis and psoriatic arthritis: An observational long term study. (23rd January 2014) - Chimenti, M.S.; Esposito, M.; Giunta, A.; Bavetta, M.; Rinaldi, M.; Chimenti, S.; Perricone, R.
Abstract : Background: Psoriasis (Pso) and psoriatic arthritis (PsA) are chronic and disabling inflammatory diseases, characterized by a chronic-relapsing and unpredictable course. Traditional systemic therapies for these conditions are limited by lack of efficacy and potential toxicity, expecially in the long-term disease management. Objectives: The present retrospective study aimed to evaluate the long-term efficacy and safety profile of subcutaneous anti-TNF agents, etanercept and adalimumab, in elderly patients (aged over 65 years) affected by PsO and PsA, including patients with comorbidities. Methods: The study included 89 patients aged more than 65 years affected by plaque-type psoriasis (27) and psoriatic arthritis (62) that received subcutaneous anti-TNF alpha agents, etanercept (61) and adalimumab (28) as monotherapy for a long-term treatment period, lasting more than 52 weeks. Results: Efficacy results were consistent as expressed by the percentage of patients who achieved and maintained PASI75 and by the improvement of articular severity indexes [pain visual analogic scale (Pain VAS) and DAS44]. Indeed, safety profile of treatment was good considering the consistent prevalence of cardiovascular and metabolic comorbidities and the long-term treatment duration. During the long-term treatment period, treatment adherence was consistent particularly for patients undergoing to etanercept, in fact among 61 patients only 15 (24.59%) treatment withdrawal were registered, while among 28 patients treated with adalimumab 11 (39.28%) treatment withdrawal were recorded. The survival rate after 3 years of treatment was 75.40% and 60.71%, for etanercept and adalimumab study population, respectively. Conclusions: Recent studies have demonstrated that PsO and PsA are associated with systemic disorders that might be sharing the same inflammatory pathway including, type 2 diabetes, obesity, hypertension, dyslipidaemia, metabolic syndrome, as well as cardiovascular disease and atherosclerosis. In elderly patients, the identification and prevention of associated risk factors as well as the systemic control of inflammation in psoriasis could result in the additional improvement of the underlying conditions. Our study demonstrated that subcutaneous anti-TNF alpha agents resulted effective in the long-term course showing an optimal safety profile considering the peculiar characteristics of patients over 65 years. The results of the present study indicate that etanercept and adalimumab may represent a valid, effective and safe therapeutic alternative even in presence of major health problems in elderly patients. References: Krueger G, Koo J, Lebwohl M et al. The impact of psoriasis on quality of life; results of a 1998 National Psoriasis Foundation patient-membership survey. Arch Dermatol 2001; 137: 280–284 Risk factors of hypertension, diabetes and obesity in Italian psoriasis patients: a survey on socio-demographic characteristics, smoking habits and alcohol consumption. Disclosure of Interest: None Declared